Hospital Responsibility for Medical Records Leaked by Medical Personnel Without the Patient's Consent - Margareth Cynthia Hutapea; Adi Bungaran Panjaitan; Sonya Airini Batubara; Jusnizar Sinaga (Dinasti Research, 2024)
Health history is a file that contains important notes or documents that contain the patient's identity regarding examinations, treatment, actions and services that have been provided to the patient. Medical records have a major influence on the legal relationship between hospitals and patients. This research examines two things, namely legal regulations related to the management of hospital patient files and the responsibility of hospitals to disclose confidential medical records. The author's aim in conducting this research is to analyze the responsibility of hospitals, especially medical personnel, if there is a data leak from a patient's medical history. This type of research is normative legal research, with emphasis on the study of legislation and literature, analyzing and revising applicable legal norms as a basis for problem solving. The research results show that the legal provisions contained in Law NO 17 of 2023 concerning health, medical personnel can be prosecuted for negligence in health services, including divulging medical secrets. Regulated in Article 301 paragraph (2) of Law NO 17 of 2023 concerning Health, medical personnel can be held responsible for actions/deeds related to the implementation of Health Services including medical records which cause civil and criminal harm to patients.